Effect of foliar application of moringa leaf extract on growth and yield of late sown wheat - Jhilik, Nusrat Zahan; Hoque, Tahsina Sharmin; Md Moslehuddin, Abu Zofar; Abedin, Md Anwarul (Asian Journal of Medical and Biological Research, 2017)
Moringa oleifera leaf extract has a potential effect as a growth enhancer of many crops. An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh, Bangladesh to evaluate the effect of foliar application of moringa leaf extract on growth and yield of late sown wheat (BARI Gom-26). The experiment was laid out in a randomized complete block design with six treatments and three replications. The treatments were T1 (Control), T2 [moringa leaf extract (MLE) sprayed only at tillering stage], T3 (MLE sprayed at tillering and jointing stages), T4 (MLE sprayed at tillering, jointing and booting stages), T5 (MLE sprayed at tillering, jointing, booting and heading stages), and T6 (MLE sprayed only at heading stage). Application of moringa leaf extract significantly increased the growth and yield attributes as well as grain and straw yield of wheat. Among various treatments with moringa leaf extract the performance of T4 (MLE sprayed at tillering, jointing and booting stages) was the best as it produced the tallest plant (87.87 cm), the highest fresh and dry weight of root (16.51 g and 11.37 g respectively), the highest number of spikelets spike-1 (19.70) and filled grains spike-1 (45.53), as well as the highest grain and straw yield (3.62 t ha-1 and 5.43 t ha-1 respectively) of wheat. Therefore, moringa leaf extract as a foliar spray can be applied at critical growth stages to increase the growth and yield potentiality of late sown wheat. Asian J. Med. Biol. Res. September 2017, 3(3): 323-329